A Review of Reference Architectures for the Next-Generation Internet of Things Systems - Gheorghe, Sorin-Daniel (EAI Endorsed Transactions on Scalable Information Systems, 2026)
The rapid evolution of the Internet of Things (IoT) demands robust architectural models capable of integrating emerging technologies and managing growing system complexity. This paper presents a structured review of IoT Reference Architectures (RAs), analysing their conceptual foundations, structural organization, and technological readiness in the context of Next-Generation IoT (NGIoT) technologies. The study examines RAs based on their support for disruptive technologies, including Edge/Fog/Cloud Computing, 5G, Artificial Intelligence, Digital Twins, Augmented Reality, Blockchain, and the Tactile Internet. Special emphasis is placed on the ASSIST-IoT RA, evaluated as a modular, cloud-native blueprint aligned with modern software design principles. Reflecting decentralization, scalability, interoperability, and resilience, ASSIST-IoT emerges as a production-ready framework for building intelligent and adaptive IoT systems. The findings synthesize current RAs trends and limitations, offering a forward-looking perspective that informs the development of NGIoT systems driven by data-driven and human-centric innovation.
Keywords: Internet of Things; Reference Architectures; Next-Generation IoT Systems; System Engineering; Industry 5.0